The Effect of Green Extract on Hemoglobin Levels in Pregnant Women with Anemia - Rahmadheny, Sucy; Fetrisia, Wiwit; Lisnira, Lisnira (Jurnal Kesehatan - STIKes Prima Nusantara, 2023)
Background: 20% of maternal fatalities are a result of anemia during pregnancy. The World Health Organization (WHO) reports that the incidence of anemia during pregnancy exceeds 56 percent. Mung bean extract contains iron, which can be used as a substitute to raise blood hemoglobin levels.Aims: The objective of this study was to determine the impact of mung bean extract on the hemoglobin levels of anemic expectant women at the Kumun Health Center in Sungai Penuh City in 2022.Methods : This is a Quasi-Experimental study with a Two-Group Pre-Test and Post-Test Design. This study's population consisted of 58 expectant women in their third trimester and a sample of 20 individuals selected using a technique of purposive sampling.Results: Prior to receiving mung bean extract and fe tablets, 10 individuals in the experimental group had Hb levels of 8.7 (Moderate Anemia), but after receiving the intervention, their Hb levels increased to 10.9. (Mild Anemia). In the control group, the Hb level of expectant women was 9.0 (Moderate Anemia) prior to receiving Fe tablets, but increased to 10.4 after receiving them (Mild Anemia).Conclusion: With a P-Value of 0.000 (0.05), it was determined that mung bean extract and Fe tablets had an effect on the hemoglobin levels of expectant women with anemia at the Kumun Health Center in Sungai Penuh City in 2022. It is recommended that pregnant women pay close attention to the foods and beverages they consume on a daily basis in order to meet their requirements during pregnancy, such as consuming beverages with high iron content, such as green bean extract and Fe tablets.